Competing and simultaneous click reactions at the interface and in solution. Issue 56 (25th May 2016) - Yiamsawas, Doungporn; Wagner, Manfred; Baier, Grit; Landfester, Katharina; Wurm, Frederik R.
Abstract : Two competing click reactions are studied in solution and at the interface of nanodroplets. By adjusting the reaction kinetics, both polyaddition (thiol–maleimide) and polycondensation (disulfide exchange) proceed simultaneously. Abstract : The kinetics of two simultaneous "click" reactions (thiol–maleimide addition and thiol–disulfide exchange) were investigated by NMR spectroscopy in homogeneous solution and at the oil/water interface of an inverse miniemulsion. For the polyaddition/-condensation of difunctional reagents it was found that the thiol–disulfide exchange is faster than the thiol–maleimide reaction. The addition of a basic catalyst influences the copolymerization behavior of the competitive "click" reactions.